Analisis Pengaruh Intensitas Persaingan dan Variabel Kontekstual Terhadap Penggunaan Informasi Sistem Akuntansi Manajemen dan Kinerja Unit Bisnis dengan Pendekatan Partial Least Squre - FAISAL FAISAL (The Indonesian Journal of Accounting Research, 2013)
This study examines the impact of intensity of market competition and contextuals variables (strategy  and perceived environmental uncertainty) on manager's use  information by management accounting system (MAS) and unit business performance. Managers' use of the information provided by management accounting systems (MAS) can help organizations  to adopt and implement plans in response to their competitive environment. In this research MAS is viewed as a system which provides benchmarking and monitoring information in addition to internal and historical information traditionally generated by management accounting system. The responses of 102 marketing dan production managers, drawn from Indonesian manufacturing companies. Data analyzed by using partial least square (PLS). The results indicate that manager's use information by management accounting system (SAM)  acts  as a mediator in the relationship between intensity of market competition and unit business performance. On the other hand, the relationship between strategy, perceived environmental uncertainty (PEU) and unit business performance through SAM are not significant.